End-of-life decision-making in the neonatal intensive care unit - Morillo Palomo, Ana; Esquerda Aresté, Montse; Riverola de Veciana, Ana; Cambra Lasaosa, Francisco José (Frontiers in Pediatrics, 2024)
Most paediatric deaths occur in the neonatal period, many of them in neonatal intensive care units after withdrawal of life support or the decision not to initiate new treatments.In these circumstances, discussions with families and decision-making are fundamental elements of the care and attention given to newborn babies. In this context, bioethical deliberation can help us to identify the values at stake, the different courses of action to be taken, and the means to ensure that family-shared decision-making is appropriate to the patient's situation and in accordance with the family's values.